Optimalisasi Pembelajaran Anak Usia Dini melalui Kegiatan Pengenalan Bahasa Inggris dan Praktikum Sains Sederhana di Nagari Paninjauan Kabupaten Solok - Zahra, Shanaz Vania; Handayani, Reysha Putri; Lestari, Indah Ayu; Hidayah, Amelia Rizkiana; Al Hakim, M. Tsaqif; Frinaldi, Aldri (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Early childhood education requires creative and interactive approaches, particularly when introducing English and conducting simple science experiments. However, instructional practices in Nagari Paninjauan have remained conventional and lacked media variety, resulting in activities that were neither routine nor interactive enough to spark children’s enthusiasm and participation. This community service initiative aimed to optimize learning by introducing English vocabulary and conducting simple science experiments. The program was implemented at the H. Abdul Moeis and Hj. Syamsiar Knowledge Park (serving TK Pertiwi 1 Paninjauan and KB Baitul Makmur Paninjauan) in Nagari Paninjauan, X Koto Diatas District, Solok Regency, involving 20 children aged 4.5 to 7 years. English instruction focused on animal vocabulary using methods such as singing, video screenings, visual aids, and mini-quiz games. Additionally, the children participated in simple experiments such as creating lava lamps, "fairy dust," and mini-volcano eruptions to foster curiosity. The results indicate that a play-based and experiment-oriented approach successfully enhanced active engagement during the learning process; this was evidenced by a 45% increase in average English vocabulary comprehension scores (rising from 40% to 85%) and an active participation rate of 90% during the experiment sessions. The activity proved effective in boosting children’s interest and understanding through a learning experience that was varied, enjoyable, and well-suited to the characteristics of early childhood learners.